Maximizing efficiency and performance of water distribution systems through the implementation of optimization algorithms: A comprehensive analysis of valve and chlorine booster placement and management - Mohamadreza Najarzadegan; Mehrtash Eskandaripour (Heliyon)
Efficient management of water distribution systems (WDSs) is critical to ensuring sustainable access to safe and reliable water. This study addresses the dual challenge of optimizing hydraulic performance and water quality in WDSs by integrating pressure management through flow control valves (FCVs) and chlorine booster optimization. By employing advanced optimization algorithms, specifically the Genetic Algorithm (GA) and Slime Mould Algorithm (SMA), the research identifies optimal configurations across two benchmark networks, Jowitt and Xu and GoYang. The results demonstrate a 15 % reduction in average pressure fluctuations and a 20 % improvement in chlorine residual uniformity, validating the effectiveness of the integrated optimization approach. Additionally, the SMA algorithm outperformed GA in terms of computational efficiency and solution quality, achieving a 12 % lower error margin and a 33 % reduction in computational time. The study also explores critical trade-offs between the number of FCVs and chlorine boosters, highlighting their impact on cost and system reliability. This work is novel in its integration of hydraulic and water quality objectives into a unified framework, which is further validated through comprehensive case studies. The findings provide practical insights for water utilities to enhance system efficiency, reduce costs, and ensure water safety while advancing the frontier of WDS optimization by addressing previously overlooked interactions between hydraulic and water quality objectives.